Energetic demand and physical conditioning of table tennis players. A study review - Moura Zagatto, A.; Kondric, M.; Knechtle, B.; Nikolaidis, P. T.; Sperlich, B. (Journal of Sports Sciences, 2017)
Table tennis is a racket sport characterised by an intermittent movement profile, including short rallies interspersed with short breaks. In contrast to other racket sports, information is lacking regarding the: (i) physiological responses during table tennis matches and training; and (ii) practical recommendations for enhancing aerobic and anaerobic performance in table tennis by improving cardio-metabolic and neuro-muscular fitness, anthropometry and nutritional strategies. Therefore, this review article attempts to narratively provide an overview of the physiology of table tennis by describing the metabolic mechanisms underlying match play and outlining a framework for practical recommendations for improving cardio-metabolic and neuro-muscular fitness, anthropometry as well as nutritional strategies. A second aim was to stimulate future research on table tennis and to point out study limitations in this context. In general, the most important finding is that the rally duration is short at around 3.5s, with a longer rest time of around 8-20s, resulting in an effort-rest ratio ranging from 0.15 to 0.22 in official matches and energetic demands during match relatively low. Future studies should focus on the relationship between energetic demand and table tennis performance with a view to predicting performance in table tennis using physiological parameters.